Jawafriend: Adaptive preservation of Javanese culture in digital platform - Yudi Pratama; Neni Wahyuningtyas; Bayu Kurniawan (Universitas Pendidikan Indonesia, 2025)
This study examines the development of a website-based learning media, Jawafriend.org, as an adaptive strategy to preserve Javanese culture in the digital era. The purpose of this study is to design, develop, and evaluate digital learning media that integrate Javanese cultural values with contemporary technological features to strengthen students' cultural understanding. This study employs a modified ADDIE model, comprising needs analysis, content and interface design, media development, implementation, and evaluation. Data were obtained through expert validation involving media, language, and material experts, using an assessment sheet that was analyzed descriptively and quantitatively to determine product feasibility by calculating validity and practicality scores using a Likert scale, with points 1-4. The results showed that Jawafriend.org achieved a validity score of 91% and a practicality score of 92%, both of which fall within the very valid and convenient categories. This platform can present cultural materials, including history, traditional houses, arts, traditional clothing, and folk games, through interactive maps, cultural quizzes, and multimedia narratives. These findings indicate that Jawafriend.org is a viable and innovative tool for cultural learning, enhancing cultural literacy, and supporting the sustainability of Javanese culture amidst globalization. Abstrak Penelitian ini mengkaji pengembangan media pembelajaran berbasis situs web, Jawafriend.org, sebagai strategi adaptif untuk melestarikan budaya Jawa di era digital. Tujuan penelitian ini adalah merancang, mengembangkan, dan mengevaluasi media pembelajaran digital yang mengintegrasikan nilai-nilai budaya Jawa dengan fitur teknologi kontemporer untuk memperkuat pemahaman budaya murid. Penelitian ini menggunakan model pengembangan ADDIE yang dimodifikasi, meliputi analisis kebutuhan, desain konten dan antarmuka, pengembangan media, implementasi, dan evaluasi. Data diperoleh melalui validasi pakar yang melibatkan pakar media, bahasa, dan materi, menggunakan lembar penilaian yang dianalisis secara deskriptif dan kuantitatif untuk menentukan kelayakan produk dengan perhitungan skor validitas dan kepraktisan menggunakan skala likert menggunanakan poin 1-4. Hasil penelitian menunjukkan Jawafriend.org mencapai skor validitas 91% dan skor kepraktisan 92%, yang keduanya termasuk dalam kategori sangat valid dan sangat praktis. Platform ini dapat menyajikan materi budaya termasuk sejarah, rumah adat, kesenian, pakaian adat, dan permainan rakyat melalui peta interaktif, kuis budaya, dan narasi multimedia. Temuan ini menunjukkan bahwa Jawafriend.org merupakan perangkat yang layak dan inovatif untuk pembelajaran budaya, meningkatkan literasi budaya, dan mendukung keberlanjutan budaya Jawa di tengah globalisasi. Kata Kunci: budaya Jawa; pelestarian budaya; platform digital